B-cell clonality and infection with Helicobacter pylori: implications for development of gastric lymphoma. Issue 6 (June 1996) - Sorrentino, D; Ferraccioli, G F; DeVita, S; Avellini, C; Beltrami, C A; Labombarda, A; Bernardis, V; De Biase, F; Trevisi, A; Pivetta, B; Boiocchi, M; Bartoli, E
Abstract : BACKGROUND: Although Helicobacter pylori has been implicated in the pathogenesis of gastric mucosa associated lymphoid tissue (MALT) and MALT lymphoma, it is not known how it may trigger these lesions and whether there is an identifiable pre-neoplastic stage. AIMS: To investigate the relation between MALT, H pylori infection, and B-cell clonality (a potential marker of pre-neoplastic lesions). PATIENTS: 141 subjects with simple dyspepsia. METHODS: Gastric biopsy specimens from all patients were examined for MALT and H pylori. Of these, 25 consecutive MALT positive specimens were scored for features of MALT lymphoma and VDJ clonality studied by polymerase chain reaction. RESULTS: Overall, prevalence was 62% for H pylori and 46% for MALT. VDJ clonality was frequent in the sub-group studied (nine of 25), mostly associated with lymphoid follicles (eight of nine or 89%), and with a high scoring for MALT lymphoma. VDJ clonality was equally frequent in patients with and without H pylori (seven of 20 and two of five or 35% and 40% respectively). CONCLUSIONS: B-cell clonality is unexpectedly common in subjects with simple dyspepsia and MALT raising clinical management questions. These findings also suggest that the cascade MALT formation--B-cell clonality--MALT lymphoma may not be uniquely associated with H pylori infection.